Multi-year monitoring of atmospheric total gaseous mercury at a remote high-altitude site (Nam Co, 4730 m a.s.l.) in the inland Tibetan Plateau region - X. Yin (Atmospheric Chemistry and Physics, 2018)
Total gaseous mercury (TGM) concentrations were continuously measured at Nam Co Station, a remote high-altitude site (4730 m a.s.l.), on the inland Tibetan Plateau, China, from January 2012 to October 2014 using a Tekran 2537B instrument. The mean concentration of TGM during the entire monitoring period was 1.33±0.24 ng m−3 (mean ± standard deviation), ranking it as the lowest value among all continuous TGM measurements reported in China; it was also lower than most of sites in the Northern Hemisphere. This indicated the pristine atmospheric environment on the inland Tibetan Plateau. Long-term TGM at the Nam Co Station exhibited a slight decrease especially for summer seasons. The seasonal variation of TGM was characterized by higher concentrations during warm seasons and lower concentrations during cold seasons, decreasing in the following order: summer (1.50±0.20 ng m−3)  >  spring (1.28±0.20 ng m−3)  >  autumn (1.22±0.17 ng m−3)  >  winter (1.14±0.18 ng m−3). Diurnal variations of TGM exhibited uniform patterns in different seasons: the daily maximum was reached in the morning (around 2–4 h after sunrise), followed by a decrease until sunset and a subsequent buildup at night, especially in the summer and the spring. Regional surface reemission and vertical mixing were two major contributors to the temporal variations of TGM while long-range transported atmospheric mercury promoted elevated TGM during warm seasons. Results of multiple linear regression (MLR) revealed that humidity and temperature were the principal covariates of TGM. Potential source contribution function (PSCF) and FLEXible PARTicle dispersion model (WRF-FLEXPART) results indicated that the likely high potential source regions of TGM to Nam Co were central and eastern areas of the Indo-Gangetic Plain (IGP) during the measurement period with high biomass burning and anthropogenic emissions. The seasonality of TGM at Nam Co was in phase with the Indian monsoon index, implying the Indian summer monsoon as an important driver for the transboundary transport of air pollution onto the inland Tibetan Plateau. Our results provided an atmospheric mercury baseline on the remote inland Tibetan Plateau and serve as new constraint for the assessment of Asian mercury emission and pollution.